Żółtlice, kolczurki, niecierpki i inne rośliny inwazyjne w Szadku - Woziwoda, Beata; Suwara-Szmigielska, Sylwia (Biuletyn Szadkowski, 2012)
Invasive alien plants are harmful non-native plant species whose introduction or spread threatens the environment, the economy, and society, including human health. They can be introduced from other continents or from one region of the same continent to another. The kenophytes are alien plants introduced to Europe after 1492. As much as 46 kenophytes have been recorded in Szadek (in years 2003-2009), what is almost 10% of the flora of the city (in total: 502 vascular plant species ). The most of "aliens" originate from the New World- from eastern and northern North America (22 species), and from northem South America and Central America (3). The species introduced from south-western, western or form central parts of Asia (19) and/or from southem, south-eastern or eastern Europe (18) are the next important group of alien plants. 27 species appear to have arrived in Europe and in Poland through intentional introductions (as ornamentals, melliferous plants, as agricultural crop etc.). The others (19 species), now recognized as weeds, have been introduced for research or as botanical curiosities (and escaped from botanical collections, gardens etc.) or they were unintentionally brought with other plant products, packing material or in ballast soil. About 70% of noted kenophytes are recognized as invasive in Poland. Some of them, e.g. “Impatiens parviflora” and “Galinsoga parviflora”, are already widespread in Szadek and poses threat native biodiversity. The others, e.g. “Echinocystis lobata” or “Reynoutriajaponica”, are rarely noted, but the growing awareness of the threats posed by these species as well as of possible risk of their invasiveness, require monitoring of localities and active prevention of their further spread.